Binding porphyrins gated dithienylethene bridge. (September 2016) - Jin, Piaopiao; Liu, Maoqi; Cao, Fei; Luo, Qianfu
Abstract: Novel porphyrins strapped with photochromic dithienylethene have been developed for photochemical double-throw gated switch. Result shows the strapped porphyrins performed totally different but reversible binding capacity and fluorescence intensity when irradiated by different lights. On the one hand, the photochromism of the dithienylethene bridge is effectively gated by porphyrin ring through binding or unbinding Zn 2+ . The central Zn 2+ in the porphyrin ring is employed as a lock, external H + as a key, which can alternately turn on/off the photochromic switch of the dithienylethene bridge. On the other hand, the porphyrin's gate for binding/unbinding Zn 2+ is reversibly regulated by dithienylethene switch with different irradiation lights. These distinctive properties might be utilized to multi-controlled molecular switches or logic gates. Graphical abstract: Highlights: Novel porphyrins axially strapped with photochromic diarylethene were constructed. The porphyrin exhibited totally different but reversible photo-chemical performances. Diarylethene bridge interacts with porphyrin ring like the lock and key of a gate.